Hubungan Flat Foot terhadap Kelincahan pada Anak Usia 7–10 Tahun - Sidarta, Nuryani; Afyora, Ririn (Jurnal Biomedika dan Kesehatan, 2024)
Background Lower extremity deformity could cause changes in the anatomical structure of the body, one of which was a flat foot. It was stated that 90%  of the clinic visits for foot problems were related to flat foot.  Studies still showed controversy regarding the relationship between flat foot and agility especially in children. This study aims to see the relationship between the incidence of flat foot and the level of agility in children aged 7 to 10 years. Methods A cross-sectional study was conducted on children aged 7-10 years who attend primary school in  Jakarta. Sampling used simple random sampling with inclusion criteria for research subjects who had a normal BMI, were cooperative, and were willing to take part in the study. Exclusion criteria included children with special needs, children with pain or a history of lower extremity injuries, those having a cavus foot, and children in unhealthy conditions. The research was carried out from February to April 2023. Assessment of flat feet used the wet footprint test and shuttle run test was being used to measure the children’s agility. Bivariate data analysis used the Chi-square test with a significance level of p <0.05. Results As 168 respondents were studied, it was found that 58.3% had flat feet. Measurement of agility with the shuttle run test results in 51.8% of respondents who have below-average agility. The results of the Chi-Square test showed that there was a significant relationship between flat feet and agility (p<0.05). Conclusions There is a relationship between flat foot and agility in children aged 7-10 years.